1999
DOI: 10.1161/01.hyp.34.3.461
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Nerve Traffic Responses to Surgical Removal of Pheochromocytoma

Abstract: Abstract-Pheochromocytoma is usually characterized by a marked increase in peripheral catecholamine secretion.Whether this is accompanied by an alteration in central sympathetic drive has not been clarified. In 6 patients with adrenal pheochromocytoma (meanϮSEM age, 49.3Ϯ7.2 years), we measured systolic and diastolic blood pressure (photoplethysmographic device), heart rate (ECG), venous plasma catecholamines (high-performance liquid chromatography), and postganglionic muscle sympathetic nerve activity (micron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 25 publications
1
8
0
1
Order By: Relevance
“…This suggests that norepinephrine may be an important determinant contributing to increased arterial stiffness in patients with PHEO. Central sympathetic outflow probably does not contribute to the alteration of arterial stiffness in pheochromocytoma, since in previous study surgical removal of the tumor resulted in an increase of central sympathetic drive 30 .…”
Section: Discussionmentioning
confidence: 77%
“…This suggests that norepinephrine may be an important determinant contributing to increased arterial stiffness in patients with PHEO. Central sympathetic outflow probably does not contribute to the alteration of arterial stiffness in pheochromocytoma, since in previous study surgical removal of the tumor resulted in an increase of central sympathetic drive 30 .…”
Section: Discussionmentioning
confidence: 77%
“…Two types of mechanisms leading to higher BP variability (especially during the daytime) in pheochromocytoma might be taken into consideration: first, the ability of circulating catecholamines to cause rapid BP elevations, and second, a high incidence of orthostatic hypotension with normally functioning baroreflex [19][20][21] probably related to the tendency to hypovolemia [22,23] or because of the suppressed central sympathetic outflow [24] as a consequence of the hyperactivation of adrenergic receptors, especially in patients with pheochromocytoma secreting norepinephrine [25].…”
Section: Discussionmentioning
confidence: 99%
“…30 Such a constellation of tachycardia, hypertension, and decreased MSNA occurs also in the fight or flight response, 31,32 after tyramine infusion, 33 and in pheochromocytoma patients. 34 It has been observed that in sleep apnea, which is associated with higher sympathetic tone; modafinil did not elevate the resting sympathetic tone further, although sympathetic effect on mental and physical load could be shown. 10 Unlike modafinil, other psychostimulants such as amphetamine elevated plasma NE, systolic and diastolic BP, but not HR or plasma Epi.…”
Section: Taneja Et Al Modafinil and Sympathetic Nervous Systemmentioning
confidence: 94%